THE EFFECT OF PRICE PERCEPTION ON CUSTOMER LOYALTY TOWARDS GORIDE IN DKI JAKARTA (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine the effect of price perception on customer loyalty to the GoRide service at PT GoTo Gojek Tokopedia Tbk in DKI Jakarta. The method used is quantitative research. Data were collected thru the distribution of questionnaires to 100 respondents selected using purposive sampling technique. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple linear regression, hypothesis tests (t-test), and the coefficient of determination (R²). The research results show that price perception has a positive and significant effect on customer loyalty. This is evidenced by the t-statistic value of 10.529, which is greater than the t-table value of 1.984 with a significance value of 0.000 (<0.05), thus H₀ is rejected and Ha is accepted. The regression coefficient of 0.954 indicates a positive influence, while the coefficient of determination (R²) value of 0.531 shows that price perception affects customer loyalty by 53.1%, while 46.9% is influenced by other factors outside the study.